Simplify: (log(40) - log(20)) + log(3)

First, know the log rule: log(x) - log(y) = log(x/y)Second, know the log rule: log(a) + log(b) = log(ab)So, starting with the brackets: log(40) -log(20) = log(40/20) which is log(2).Now we have: log(2) + log(3).So, using the other log rule we can do: log(2) + log(3) = log(23) which is log(6).Therefore, (log(40) - log(20)) + log(3) = log(6)

Answered by Edward R. Maths tutor

3017 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Why do we need to differentiate?


Differentiate x^2


Given that dx/dt = (1+2x)*4e^(-2t) and x = 1/2 when t = 0, show that ln[2/(1+2x)] = 8[1 - e^(-2t)]


Give the first and second derivative of the function f(x) = 5/x - 9x + 4


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences